A Comparative study on efficacy of Granisetron and Ondansetron in the Prevention of Post- Operative Nausea and Vomiting after Laparoscopic surgery - Sharma, M.; Sapkota, S.; Sharma, S.; Shakya, S. (Devdaha Medical Journal, 2024)
Introduction: Postoperative nausea and vomiting (PONV) are a common surgical complication. Risk factors include, type, and patient-specific factors like young females, duration of anaesthesia (>30 min), type of surgical procedure, history of motion sickness or a family past history of PONV. Effective management with 5-HT3 antagonists, such as ondansetron and granisetron, improves patient recovery, reduces discomfort and days of hospitalization. The current study’s objective is to evaluate the efficacy of Granisetron and Ondansetron in preventing PONV in patients having laparoscopic procedures. Methods: This is prospective interventional study at Nepalgunj Medical College involved 80 patients scheduled for laparoscopic surgery. Participants aged 15-55 with American society of anaesthesiologist (ASA) grades I and II received either ondansetron 4mg intravenous (group A) or granisetron 2 mg intravenous (Group B) before anaesthesia. Postoperatively, patients were monitored for nausea, vomiting, and need for rescue antiemetics. Adverse effects were recorded during a 24-hour observation period. Written informed consent was obtained from all participants. Results: There were no statistical differences between the two groups in terms of gender, age, weight, or surgery type (p > 0.05). Group B experienced a significantly lower incidence of PONV (25%) compared to Group A (55%) with a p-value of 0.03. During the 0–6-hour period, 90% of Group B and 75% of Group A had no PONV (p = 0.18). No significant differences were observed between the 6-12- and 12-24-hour intervals. Conclusion: The study concludes that Granisetron prevents PONV better than Ondansetron in patients undergoing laparoscopic surgery when given 2 mins just prior to induction of anaesthesia.